Aggregation‐Prone Amyloid‐β⋅CuII Species Formed on the Millisecond Timescale under Mildly Acidic Conditions. Issue 9 (18th May 2015) - Pedersen, Jeppe T.; Borg, Christian B.; Michaels, Thomas C. T.; Knowles, Tuomas P. J.; Faller, Peter; Teilum, Kaare; Hemmingsen, Lars
Abstract Metal ions and their interaction with the amyloid beta (Aβ) peptide might be key elements in the development of Alzheimer's disease. In this work the effect of CuII on the aggregation of Aβ is explored on a timescale from milliseconds to days, both at physiological pH and under mildly acidic conditions, by using stopped‐flow kinetic measurements (fluorescence and light‐scattering), 1H NMR relaxation and ThT fluorescence. A minimal reaction model that relates the initial CuII binding and Aβ folding with downstream aggregation is presented. We demonstrate that a highly aggregation prone Aβ⋅CuII species is formed on the sub‐second timescale at mildly acidic pH. This observation might be central to the molecular origin of the known detrimental effect of acidosis in Alzheimer's disease.